IMPLEMENTATION OF INDONESIAN LEARNING STORY SKILL OF CARTOON PUPPET MEDIA OF STUDENT OF GRADE IV OF STATE PRIMARY SCHOOL - Vivi Rulviana (Universitas PGRI Madiun, 2016)
The objective of this research is to investigate the planning and implementation telling skill the use of cartoon puppet media of the student in Grade IV of State Primary School of Tladan 2, Kawedanan, Magetan.This research used the qualitative research method. The source of this research were Principal, Class Teacher of Grade IV, and the students in Grade IV by using interview, and observation. They were analyzed by using the interactive model of analysis comprising data reduction, data display, and conclusion drawing of verification.The results of research are as follows: 1) the planning of telling by teacher with preparing the annual program, the semester program, the details of effective weeks, the journal of teaching, lesson plan, syllabus development and the development of assessment systems, 2) Implementation of the learning skills of telling is packed with a variety of methods and media puppet cartoon. Teachers began teaching with fun activities for the creation of learning readiness, motivation and interest in learning in students. Teachers utilized cartoon puppet media in learning storytelling in the fourth grade to get a great result for students for example: interested in learning, motivation, self-confidence and have the ability to tell a coherent accordance with the storyline.